2018
DOI: 10.1093/ndt/gfy100
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3 in aberrant endothelial secretome triggers renal fibroblast activation and endothelial–mesenchymal transition

Abstract: In conclusion, this unbiased proteomic screen of the profibrogenic endothelial secretome revealed DKK3 acting as an agonist of the Wnt pathway, enhancing formation of myofibroblasts and endothelial-mesenchymal transition and impairing angiogenesis. A potent inhibitor of the Wnt pathway, sulindac sulfide, suppressed nephropathy-induced DKK3 expression and renal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…It was concluded that the secretome partly mediates protection from LPS-induced AKI. Later studies showed that endothelium-derived humoral factors are also involved in renal fibrogenesis [25]. In the 2015 published article [24] In the last paragraph will would like to discuss our proteomic data.…”
Section: Discussionmentioning
confidence: 98%
“…It was concluded that the secretome partly mediates protection from LPS-induced AKI. Later studies showed that endothelium-derived humoral factors are also involved in renal fibrogenesis [25]. In the 2015 published article [24] In the last paragraph will would like to discuss our proteomic data.…”
Section: Discussionmentioning
confidence: 98%
“…It was concluded that the secretome partly mediates protection from LPS-induced AKI. Later studies showed that endothelium-derived humoral factors are also involved in renal fibrogenesis [25]. In the 2015 published article [24] one essential problem related to any cell-based therapeutic approach in AKI was emphasized: the problem of cell delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proximal tubules with tamoxifen-induced Wnt1 expression have profound interstitial myofibroblast activation and proliferation and increased extracellular matrix proteins production ( Maarouf et al, 2016 ). We showed that DKK3 is able to convert fibroblasts into myofibroblasts with DKK3 being secreted by SIRT1 deficient endothelial cells ( Lipphardt et al, 2018a ). We also investigated the relations between DKK1 and DKK3 and learned that DKK3 is only able to activate fibroblasts to acquire myofibroblastic phenotype at low levels of DKK1.…”
Section: Agonists Of Notch and Wnt Pathways In The Secretomementioning
confidence: 99%
“…Having demonstrated the effects of DKK3 and Jagged1 secreted from dysfunctional endothelial cells exerting paracrine effects on renal fibroblasts, it was only plausible to expect their autocrine effects. In experiments on DKK3 application to cultured RMVEC we found that DKK3 significantly increased the amount of RMVEC undergoing endothelial-mesenchymal transition ( Lipphardt et al, 2018a ). We also showed that RMVEC cultured on matrigel exhibited reduced total vessel length, percentage area occupied by capillary-like structures, and limited number of bifurcations after treatment with DKK3 ( Lipphardt et al, 2018a ).…”
Section: Autocrine Effects Of Endothelial Secretomementioning
confidence: 99%
See 1 more Smart Citation